1987
DOI: 10.1111/j.1095-8312.1987.tb01984.x
|View full text |Cite
|
Sign up to set email alerts
|

The biological roles of pyrazines: evidence for a warning odour function

Abstract: Recently it has been shown that pyrazines are associated with many aposematic, chemically defended insects. We have demonstrated that naive hatchling chicks, when offered drinking water to which 2‐methoxy‐3‐isobutylpyrazine is added, develop a neophobic ‘alerting’ reaction. The birds are not only capable of forming a conditioned aversion to the pyrazine when it is paired with quinine sulphate but they can also detect it from a distance probably by olfaction. This suggests that birds, a major group of insect pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(74 citation statements)
references
References 27 publications
2
72
0
Order By: Relevance
“…It is likely that if large amounts of volatiles are produced by A. pagana L5-6, which display aposematic body colours, then they may function more easily as a defence, not only towards invertebrates such as ants, but also towards predatory birds, as chemical warning signal. Such a function is known for odours emitted by caterpillars (Guilford et al, 1987). Beside a physical protection (see above), the L5-6 of A. pagana would combine visual and chemical warning signals.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that if large amounts of volatiles are produced by A. pagana L5-6, which display aposematic body colours, then they may function more easily as a defence, not only towards invertebrates such as ants, but also towards predatory birds, as chemical warning signal. Such a function is known for odours emitted by caterpillars (Guilford et al, 1987). Beside a physical protection (see above), the L5-6 of A. pagana would combine visual and chemical warning signals.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant findings of seven experimental studies documenting the responses of supposedly naive predators to real aposematic prey with defenses known to induce aversion (in all but two studies* learned aversion had been demonstrated). Subsidiary data are from: Rothschild (1985)1, Brower (1984)2, Davis and Nahrstedt (1985)3, Guilford et al (1987)4. The table does not include studies which are anecdotal or poorly controlled, do not document predator responses to first presentations, use artificial prey, or use predators likely to have had prior experience with the relevant prey or prey from which aversive responses may have been generalized.…”
Section: Immediate Versus Delayed-action Toxinsmentioning
confidence: 99%
“…Birds can detect pyrazine, and learn to avoid unpalatable prey by odour alone (Guilford et al 1987;see Roper (1999) for a review of birds' olfactory capabilities), but pyrazine can also evoke unlearned colour biases in naive avian predators. Pyrazine odour causes naive domestic chicks (Gallus gallus domesticus) to reduce their intake of prey that share visual characteristics typical of aposematic insects, such as prey that are red or yellow (Rowe & Guilford 1996, con-spicuous against the background (Lindströ m et al 2001), or novel in appearance ( Jetz et al 2001).…”
Section: Introductionmentioning
confidence: 99%